2014
DOI: 10.4103/0972-5229.138157
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemic paralysis in primary adrenal insufficiency

Abstract: Hyperkalemic paralysis due to Addison's disease is rare, and potentially life-threatening entity presenting with flaccid motor weakness. This case under discussion highlights Hyperkalemic paralysis as initial symptomatic manifestation of primary adrenal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hyperkalemic periodic paralysis has been described in two forms: primary hyperkalemic periodic paralysis and secondary hyperkalemic periodic paralysis. Primary hyperkalemic paralysis (hyperkalemic periodic paralysis) is an inherited autosomal dominant disorder that impairs sodium channel function in skeletal muscle cells and thereby reduces the ability to regulate potassium levels [ 2 ]. Secondary hyperkalemic periodic paralysis is the acquired form of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperkalemic periodic paralysis has been described in two forms: primary hyperkalemic periodic paralysis and secondary hyperkalemic periodic paralysis. Primary hyperkalemic paralysis (hyperkalemic periodic paralysis) is an inherited autosomal dominant disorder that impairs sodium channel function in skeletal muscle cells and thereby reduces the ability to regulate potassium levels [ 2 ]. Secondary hyperkalemic periodic paralysis is the acquired form of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…With secondary hyperkalemic periodic paralysis, neurophysiological testing has revealed that although there is normal muscle fiber activity, there is an interruption in nerve conduction rate within the skeletal muscle. Secondary hyperkalemic periodic paralysis is most commonly seen in patients with acute or chronic renal dysfunction, Addison’s disease, rhabdomyolysis, or excessive ingestion of potassium supplements or potassium-rich foods such as bananas or potatoes [ 2 ]. Our patient, unfortunately, had not received any dietary education since her diagnosis of ESRD six months prior and, as a result, continued to ingest large quantities of potatoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation